The Relationship Between Employee Engagement And Employee Performance In The Banking Sector Of Haryana (Journal of Namibian Studies : History Politics Culture, 2023)
Employee engagement has become a very common managerial concept in the current day.  Most organizations employ a diversity of engagement-building tools to increase performance and face the competition. Even though the term employee engagement is being argued more and more in human resource-referring firms, there aren't many research studies on it, especially in nations with growing economies. The main aim of this research paper is to know the association between employee engagement and employee performance in the public and private banks of Haryana. The research sample included 480 respondents working in SBI, PNB, HDFC and ICICI Banks. Established measures are included in the questionnaire relating to employee engagement and employee performance and also include some demographic questions. This research study was descriptive that is carried out in 4 Banks of Haryana. A questionnaire was used for data collection and Karl Pearson's coefficient of correlation test was applied to find out the relationship between them. employee engagement and employee performance. Data analysis was done through SPSS 25 statistical software. The findings indicated a positive and significant relationship between employee engagement and employee performance.   (r = .801, p = 0.002< 0.05). Improving employee engagement practices in banks could be a valuable strategy for enhancing employee performance.